Zenith sky brightness and celestial objects visibility during total solar eclipse on March 9, 2016 at Terentang Beach Bangka Island - Wijaya, A. F. C. (2018)
This paper endeavor to describe sky brightness measurements which was carried out by a team of total solar eclipse observers (TOGEMA) on 9th March 2016. The observations took place at Tarentang Beach, Bangka Island and it utilized the SQM-LU instrument (Sky Quality Meter- USB Connector) with 1 second time interval data. During total phase that lasted about 1 minute 52 seconds, the instrument recorded the brightness of the sky of 12.88 mag/["]2 as the dimmest value. This value is approximately 500 times brighter than the dimmest night sky conditions at the same location, obtained on the previous observation. It was found that the brightest sky that could be measured by SQM-LU during Total Solar Eclipse (TSE) 2016 was 5.91 mag/["]2. The activity with digital camera also captured the appearance of Venus and Mercury. The appearance of Venus (-3.71 mag) confirmed naked eye limited magnitude theory. This may explain the inability of observers to perceive Mercury (0.46 mag) using naked eye during the total phase of solar eclipse.